Digitalization in Knowledge Management Systems for Project and Operational Management in Software Development to Increase Efficiency - Fransisca Cahyono; Jann Hidajat Tjakraatmadja (Research Synergy Foundation, 2022)
PT Snack Sehat is a manufacturing company that produces healthy snacks and beverages in Indonesia. Its IT division has a software department that manages all creation and maintenance of information system projects. Although the software department planned and monitored project development thoroughly during their work, 42% of projects were late in 2020. Those late projects' costs led to financial loss and kept rising through 2020-2021. Digitalization is how technologies affect several aspects of life, like social interactions, business operations, and how people work. Digitalization improved and sped up knowledge-sharing processes within the organization. Since knowledge sharing is done more frequently, the absorptive capacity will also be improved. This brings up the question of how to design a KM program with digital tools that will help PT Snack Sehat to increase its efficiency in project development and operation support. The primary data for this research was gathered from KM Assessment using APO KM Framework and focus group discussion with top and middle-level managers from PT Snack Sehat. To develop a KM program, the research will use Six Steps KM Processes, which consist of KM Project, KM Assessment, KM Planning, K-Development, KM Implementation, and KM Evaluation. The development steps will include defining the objectives of the KM program, answering questions related to the knowledge management components (people, process, and technology), determining the knowledge management strategy based on KM objectives, and setting the action plan to get ten commitments from top-level management. The results show several processes and methods that need to be added to the current KM: KM Orientation & Training, Shadowing, Sharing Knowledge Checklist, Lesson Learned Document, Document Validation, and Document Organization. The complete knowledge management process will also be mapped in a Knowledge Stock and Flow Diagram using SECI Matrix. Keywords: Project Development, Operational Management, Six Steps KM Processes, SECI Matrix, Digitalization, Absorptive Capacity, Efficiency